Potential of immune-related genes as promising biomarkers for premature coronary heart disease through high throughput sequencing and integrated bioinformatics analysis - Wang, Haiming; Shao, Junjie; Lu, Xuechun; Jiang, Min; Li, Xin; Liu, Zifan; Zhao, Yunzhang; Zhou, Jingjing; Lin, Lejian; Wang, Lin; Xu, Qiang; Chen, Yundai; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary heart disease (CHD) is the most common progressive disease that is difficult to diagnose and predict in the young asymptomatic period. Our study explored a mechanistic understanding of the genetic effects of premature CHD (PCHD) and provided potential biomarkers and treatment targets for further research through high throughput sequencing and integrated bioinformatics analysis. Methods: High throughput sequencing was performed among recruited PCHD patients and young healthy individuals, and CHD-related microarray datasets were obtained from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified by using R software. Enrichment analysis and CIBERSORT were performed to explore the enriched pathways of DEGs and the characteristics of infiltrating immune cells. Hub genes identified by protein–protein interaction (PPI) networks were used to construct the competitive endogenous RNA (ceRNA) networks. Potential drugs were predicted by using the Drug Gene Interaction Database (DGIdb). Results: 35 DEGs were identified from sequencing dataset and GEO database by the Venn Diagram. Enrichment analysis analyses indicated that DEGs are mostly enriched in excessive immune activation pathway and signal transduction. CIBERSORT exhibited that resting memory CD4 T cells and neutrophils were more abundant, and M2 macrophages, CD8 T cells, naïve CD4 T cells were relatively scarce in PCHD patients. After identification of ten hub gens, three ceRNA networks of CD83, CXCL8 and NR4A2 were constructed by data retrieval and validation. In addition, CXCL8 might interact most with multiple chemical compounds mainly consisting of anti-inflammatory drugs. Conclusions: The immune dysfunction mainly contributes to the pathogenesis of PCHD, and three ceRNA networks of CD83, CXCL8 and NR4A2 might be potential candidate biomarkers for early diagnosis and treatment targets of PCHD.